Determinants Transact Using Bi Fast Transfer Service On Bsi Mobile - Lubis, Rahmat Husein; Hasniati (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2023)
The current development of technology 4.0 shows the progress of application transactions in Islamic financial institutions. It does not rule out possibilities like BSI Mobile with its BI Fast service. BI Fast service is a transfer transaction service between Bank Syariah Indonesia and other conventional banks with a fee of Rp. 2,500 per transaction. The research used is quantitative research with primary and secondary data. Data collection is carried out by distributing questionnaires. The sampling technique is a random sampling technique of 30 respondents from UIN students Prof. K. H. Saifuddin Zuhri Purwokerto. The data analysis used is a reliability test, validity test, basic assumption test (normality test, descriptive analysis test, and linearity test). Then for hypothesis tests using (t test, F test, and R2 determination coefficient test) and multiple tests. For data management, it uses the SPSS 25 application in 2023. Use of BI Fast application on BSI Mobile. Based on the data processing, it was concluded that there is an influence of financial literacy on transactions using BI Fast BSI Mobile services, there is no effect of convenience on transactions using BI Fast BSI Mobile services, and there is no influence of trust on transactions using BI Fast BSI Mobile services. And simultaneously the three variables of financial literacy, convenience, and trust do not affect transactions using BI Fast BSI Mobile services